The effectiveness and characteristics of pregnancy yoga interventions: a systematic review protocol - Eustace-Cook, Jessica; Daly, Deirdre (My University, 2020)
Background: The purpose of this review is to systematically examine the reported clinical effectiveness of pregnancy yoga. The review will use the FITT (frequency, intensity, time/duration and type) principle of physical activity to characterise the different types of yoga interventions that have been evaluated in the included studies. Studies will be categorised as effectiveness or efficacy studies and this continuum of efficacy versus effectiveness will be incorporated into the full review. Methods/design: The following electronic databases will be searched using a detailed search strategy: MEDLINE, PsycINFO, EMBASE, CINAHL, WHOLiS, AMED, ScieLo, ASSIA and Web of Science. Randomised control trials and quasi-experimental studies examining pregnancy yoga and reporting on effect will be included. Titles, abstracts and full articles will be screened by two investigators independently to identify eligible studies. The Cochrane Collaboration's Risk of Bias Assessment tool will be used to assess study quality. Quality of the evidence will be evaluated using the GRADE criteria. A standardised data extraction form will be used to extract data. Effect sizes will be estimated using mean differences for continuous outcomes, and relative risks for dichotomous outcome. Where possible, pooling of effect estimates will be done using a random effect model. The outcomes of interest are quality of life, stress, anxiety, depression, mode of birth, labour duration and pain management in labour. Discussion: This review will synthesise the best available evidence on the effectiveness of yoga during pregnancy and provide valuable high-quality information for clinicians and health policymakers. Findings will be disseminated through publication in a peer-reviewed journal and presentation at relevant conference proceedings. The review will make recommendations for the appropriate volume, intensity and type of pregnancy yoga for maximum effect and may have implications for policy and practice relating to pregnancy yoga as an intervention.
PUBLISHED
Keywords: Pregnancy; Yoga; Systematic review; Intervention